PENGEMBANGAN MODEL PEMBELAJARAN PAIR CHECK BERBASIS CABI (PECAHAN PADA UBIN) DALAM PEMBELAJARAN MATEMATIKA MATERI PECAHAN SISWA KELAS V SEKOLAH DASAR KECAMATAN DONOROJO - Yessy Nusantarawati (COLLASE (Creative of Learning Students Elementary Education), 2023)
This study has the objectives to be achieved, namely analyzing the effectiveness of the cabi based Pair Check Model in learning mathematics with fractions for grade V students. This study uses the type of Research and development (R&D) This research activity began with a product feasibility trial using research samples at SDN 1 Clering, SDN 3 Clering and SDN 3 Ujungwatu as the experimental class and SDN 2 Clering as the control class. Data were collected using observation, interview, documentation, questionnaire and test techniques. Data on the effectiveness of this Cabi-based Pair Check learning model were analyzed using a gain test and a sample test assisted by the SPSS program. Analysis of the needs for the development of the Cabi-based Pair Check model is known through the analysis of teacher needs and analysis of student needs. The results of the study is the cabi-based pair check model is quite effective in improving the learning outcomes of fifth grade students in mathematics in addition and subtraction of fractions with n gain in the medium category and interpretation is quite effective with a percentage of 64.46%. The conclusion of this study is that the development of a pair check model based on fractions on tiles (cabi) can improve the learning outcomes of addition and subtraction of fractions in fifth grade elementary school students.